The direct first pass aspiration technique in the treatment of acute ischemic stroke resulting from large vessel occlusions - Castro-Afonso, Luís Henrique de; Nakiri, Guilherme Seizem; Monsignore, Lucas Moretti; Cougo-Pinto, Pedro Telles; Dias, Francisco Antunes; Aléssio-Alves, Frederico; Pontes-Neto, Octávio Marques; Abud, Daniel Giansante (Arquivos de Neuro-Psiquiatria, 2017)
Mechanical thrombectomy using stent retrievers is the standard treatment for acute ischemic stroke that results from large vessel occlusions. The direct aspiration first pass technique (ADAPT) has been proposed as an efficient, fast, and cost-effective thrombectomy strategy. The aim of this study was to assess the safety and efficacy of ADAPT. Recanalization was assessed using the modified thrombolysis in cerebral infarction (mTICI) score. Neurological outcomes were assessed using the National Institutes of Health Stroke Scale and modified Rankin Scale.Fifteen patients were evaluated. The mTICI score was 2b-3 in 80%, and it was 3 in 60% of patients. No intracranial hemorrhage was seen. At three months, modified Rankin Scale scores ≤ 2 were observed in 60% of patients and the mortality rate was 13.3%.The ADAPT appears to be a safe, effective, and fast recanalization strategy for treatment of acute ischemic stroke resulting from large vessel occlusions.
Keywords: stroke; stents; catheters